Negative plate and lithium ion battery
By adopting a negative electrode sheet with a double-layer coating structure in a lithium-ion battery, the first coating of non-carbon-encapsulated graphite and microporous vapor-phase silicon carbon and the second coating of carbon-encapsulated graphite and silicon oxide, the problem that the capacity of the existing battery negative electrode materials is close to the limit, and the battery energy density and fast charging performance are improved.
Patent Information
- Application Number
- CN202510300171.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-13
- Publication Date
- 2025-06-27
AI Technical Summary
The capacity of the negative electrode material of existing lithium-ion batteries is close to its theoretical limit, making it difficult to further improve the energy density and fast charging capacity of the battery, and the cycle performance is insufficient.
The negative electrode sheet with a double-layer coating structure is adopted. The first coating uses non-carbon-encapsulated graphite and microporous vapor-phase silicon carbon, and the second coating uses carbon-encapsulated graphite and silicon oxide. By optimizing the composition and structure of the active material, the energy density and fast charging performance of the battery are improved.
It achieves the simultaneously improved the energy density, fast charging performance and cycling performance of the battery, and improved the gram capacity of the negative electrode material and the overall performance of the battery.
Smart Images

Figure CN120221569A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of batteries, specifically to a negative electrode sheet and a lithium-ion battery. Background Art
[0002] New energy vehicles currently mainly use lithium-ion batteries as power batteries. While their sales are growing rapidly, higher requirements are also put forward for their performance, such as driving range, charging time, safety issues, low-temperature performance, service life, etc. Among them, improving the driving range requires increasing the energy density of the battery, and increasing the energy density requires increasing the specific capacity and voltage of the positive and negative electrode materials of the battery. As for the negative electrode material, currently it is mainly graphite material, and the specific capacity that can be exerted has approached its theoretical specific capacity. In order to further significantly increase the specific capacity of the negative electrode material, people have turned their attention to silicon materials.
[0003] Silicon and carbon belong to the same group of elements. Different from the lithium storage mechanism of graphite intercalation and deintercalation of lithium, silicon completes lithium storage by forming a silicon-lithium alloy with lithium ions. Its highest specific capacity can reach 3579 mAh / g at room temperature, greatly increasing the upper limit of the specific capacity of the negative electrode material. However, the problem with this lithium storage mechanism is that the volume change during the intercalation and deintercalation of lithium is very large. After continuous efforts, the silicon negative electrode materials that can be actually applied are mainly ground silicon, silicon monoxide, pre-lithiated / magnesium pre-lithiated silicon monoxide, and new vapor-phase silicon carbon, etc. They are actually applied to the battery negative electrode sheet by blending with graphite material in different proportions. While increasing the energy density of the battery, people hope to further improve the fast charging ability and cycling performance, which puts forward higher requirements for the selection of the negative electrode material and the overall design and use of the electrode sheet, and urgently needs to be solved by people. Summary of the Invention
[0004] In view of this, the present invention provides a negative electrode sheet and a lithium-ion battery. This negative electrode sheet can simultaneously improve the energy density, fast charging performance, and cycling performance of the battery.
[0005] In order to achieve the above invention purpose, the present invention provides the following technical solutions:
[0006] In the first aspect, the present invention provides a negative electrode sheet, which includes a current collector, a first coating, and a second coating. The first coating is disposed on two surfaces in the thickness direction of the current collector, and the second coating is disposed on the surface of the first coating away from the current collector;
[0007] The first coating includes a first active material, and the first active material includes non-carbon-coated graphite and microporous vapor-phase silicon carbon;
[0008] The second coating includes a second active material, and the second active material includes carbon-coated graphite and silicon monoxide.
[0009] Preferably, the specific capacity of the non-carbon-coated graphite is 352 to 358 mAh / g, and the maximum tap density is 1.65 to 1.75 g / cm 3 , and the value of I D / I G in the Raman spectrum ranges from 0.1 to 0.3, and the median particle size is 9 to 18 μm.
[0010] Preferably, the non-carbon-coated graphite is single-particle graphite or secondary-particle graphite.
[0011] Preferably, the non-carbon-coated graphite is single-particle graphite.
[0012] Preferably, the non-carbon-coated graphite is needle coke-based graphite.
[0013] Preferably, the specific capacity of the carbon-coated graphite is 343 to 349 mAh / g, and the maximum tap density is 1.55 to 1.65 g / cm 3 , and the value of I D / I G in the Raman spectrum ranges from 0.8 to 1.2, and the median particle size is 9 to 18 μm.
[0014] Preferably, the carbon-coated graphite is single-particle graphite or secondary-particle graphite.
[0015] Preferably, the carbon-coated graphite is secondary-particle graphite.
[0016] Preferably, the carbon-coated graphite is petroleum coke-based graphite.
[0017] Preferably, the specific capacity of the microporous gas-phase silicon carbon is 1800 to 2000 mAh / g, the initial Coulombic efficiency is 90% to 93%, and the median particle size is 6 to 10 μm.
[0018] Preferably, the pore volume of the microporous gas-phase silicon carbon is 0.6 to 1.0 cm 3 / g, the pore diameter of the micropores of the microporous gas-phase silicon carbon is 0.4 to 2 nm, and the volume ratio of the micropores in the total pore volume of the microporous gas-phase silicon carbon is 90% to 96%.
[0019] In the embodiments of the present invention, the carbon source of the carbon substrate of the microporous gas-phase silicon carbon includes at least one of biomass-based carbon sources, resin-based carbon sources, and coke-based carbon sources.
[0020] Preferably, the specific capacity of the silicon suboxide is 1300 to 1500 mAh / g, the initial Coulombic efficiency is 89% to 92%, and the median particle size is 4 to 8 μm.
[0021] Preferably, the silicon suboxide is pre-lithiated silicon suboxide and / or pre-magnesium silicon suboxide.
[0022] Preferably, the silicon crystal domain size of the silicon suboxide is 5 to 9 nm.
[0023] Preferably, the mass ratio of the microporous gas-phase silicon carbide in the first active material is 10% to 50%.
[0024] Preferably, the mass ratio of the silicon monoxide in the second active material is 10% to 50%.
[0025] Preferably, the specific capacity of the first active material is 600 to 700 mAh / g.
[0026] Preferably, the specific capacity of the second active material is 600 to 700 mAh / g.
[0027] In an embodiment of the present invention, the first coating further includes a first binder and a first conductive agent.
[0028] In an embodiment of the present invention, the second coating further includes a second binder and a second conductive agent.
[0029] In an embodiment of the present invention, the first binder and the second binder independently include a type-A binder and a type-B binder.
[0030] In an embodiment of the present invention, the type-A binder includes at least one of polyacrylic acid, polyacrylonitrile, sodium carboxymethyl cellulose, and lithium carboxymethyl cellulose.
[0031] In an embodiment of the present invention, the type-B binder includes at least one of styrene-butadiene rubber and modified styrene-butadiene polymer.
[0032] In an embodiment of the present invention, the first conductive agent and the second conductive agent independently include a type-C conductive agent and a type-D conductive agent.
[0033] In an embodiment of the present invention, the type-C conductive agent includes at least one of single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, and graphdiyne.
[0034] In an embodiment of the present invention, the type-D conductive agent includes at least one of acetylene black, Ketjen black, Super P, and EnsacoTM.
[0035] Preferably, in the first coating, the mass ratio of the first active material, the first binder, and the first conductive agent is (90 - 95):(5 - 10):(1 - 5).
[0036] Preferably, in the second coating, the mass ratio of the second active material, the second binder, and the second conductive agent is (95 - 100):(1 - 5):(0.5 - 1.5).
[0037] Preferably, the ratio of the mass ratio of the first binder in the first coating to the mass ratio of the second binder in the second coating is (1 - 4):1.
[0038] Preferably, the ratio of the mass percentage of the first conductive agent in the first coating to the mass percentage of the second conductive agent in the second coating is (1-4):1.
[0039] Preferably, the mass ratio of the first coating to the second coating is 1:(0.5-2).
[0040] Preferably, the ratio of the porosity of the second coating to the porosity of the first coating is (1-2):1.
[0041] Preferably, the compaction density of the negative electrode sheet is 1.5-1.7 g / cm 3 .
[0042] In a second aspect, the present invention provides a lithium-ion battery, which includes the above-mentioned negative electrode sheet.
[0043] Compared with the prior art, the beneficial effects of the present invention are:
[0044] In the present invention, by designing a negative electrode sheet structure with a double-layer coating, the energy density and fast charging performance of the battery are improved simultaneously. For a battery with a specific size, the addition of silicon material with a higher specific capacity in the negative electrode sheet can reduce the coating weight of the active material, thereby improving the energy density of the battery. In order to improve the energy density and fast charging performance simultaneously, the present invention designs a double-layer coated electrode sheet structure, in which the first coating selects non-carbon-coated graphite, and the raw material is needle coke, which has a higher degree of graphitization, a higher capacity, and a larger maximum compaction density, and can improve the energy density; and the microporous gas-phase silicon-carbon material in the first coating can further improve the specific capacity of the active material, and has a smaller volume expansion and contraction during the cycling process compared with the silicon monoxide material in the second coating, and has a higher cycling stability. The second coating selects carbon-coated graphite. After carbon coating, the degree of graphitization on the surface is weakened, and the I D / I G increases, and the kinetic performance of lithium deintercalation and insertion is enhanced. Moreover, the raw material of carbon-coated graphite is petroleum coke, with more mosaic structures and better isotropy, which also helps to improve the kinetic performance; the silicon monoxide material paired with it has a lower capacity and cycling stability compared with the microporous gas-phase silicon-carbon material in the first coating, but its kinetic performance is better, especially showing a lower DC internal resistance at the end of discharge, which improves the fast charging performance.
[0045] On the other hand, the particle strength of the active material in the second coating of the present invention is higher than that of the first coating, which can well conduct the force downward during the rolling of the electrode sheet, improve the processing stability of the electrode sheet, obtain an electrode sheet with a larger compaction density, and improve the energy density of the battery.
[0046] In addition, the design of the binder, conductive agent, and porosity in the electrode is also to further improve the energy density and fast charging performance of the battery simultaneously. When the electrode coating is dried, due to the capillary force, the binder will migrate to the surface. Moreover, with the increase in coating speed and coating thickness, the migration of the binder during the drying process becomes more serious, which will further weaken the adhesion between the dressing and the current collector, having a negative impact on the battery performance. Considering this problem, in the double-layer coating structure of the present invention, a higher mass ratio of the binder is used in the first coating slurry for compensation in advance. And the first coating has a higher content of the conductive agent, which can form more conductive paths, reduce the electron transfer resistance of the electrode, and improve the battery rate performance and cycle stability. The porosity of the second coating is greater than that of the first coating, which is beneficial to the migration of lithium ions inside the thick electrode, thereby obtaining better electrochemical performance at high current densities. Description of the Drawings
[0047] Figure 1 The step charging rate test results for the examples and comparative examples. Detailed Description of the Invention
[0048] The present invention discloses a negative electrode sheet and a lithium-ion battery. Those skilled in the art can draw on the content of this article and appropriately modify the process parameters to achieve it. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all regarded as included in the present invention. The methods and applications of the present invention have been described through preferred embodiments. Relevant personnel can obviously make changes or appropriate alterations and combinations to the methods and applications described herein without departing from the content, spirit, and scope of the present invention to implement and apply the technology of the present invention.
[0049] In the description of the present invention, it should be noted that the terms "first", "second", etc. are only used for descriptive purposes and do not indicate or imply relative importance.
[0050] In the description of the present invention, the list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0051] The endpoints and any values within the ranges disclosed herein are not limited to the exact ranges or values. These ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, between the endpoint values of each range, between the endpoint value of a range and a single point value, and between single point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be considered to be specifically disclosed herein.
[0052] If there is no special indication, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0053] If there is no special indication, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.
[0054] If there is no special indication, the "including" and "comprising" mentioned in the present application mean open-ended, and can also be closed-ended. For example, the "including" and "comprising" can mean that other components not listed can also be included or comprised, or can only include or comprise the listed components.
[0055] Specifically, the present invention adopts the following technical solutions:
[0056] In a first aspect, the present invention provides a negative electrode sheet, which includes a current collector, a first coating, and a second coating. The first coating is disposed on two surfaces in the thickness direction of the current collector, and the second coating is disposed on the surface of the first coating away from the current collector;
[0057] The first coating includes a first active material, and the first active material includes non-carbon-coated graphite and microporous gas-phase silicon carbon;
[0058] The second coating includes a second active material, and the second active material includes carbon-coated graphite and silicon monoxide.
[0059] In the present invention, by designing a negative electrode sheet structure with a double-layer coating, the energy density and fast charging performance of the battery are improved simultaneously. For a battery with a specific size, the addition of a silicon material with a higher specific capacity in the negative electrode sheet can reduce the coating weight of the active material, thereby improving the energy density of the battery. In order to improve the energy density and fast charging performance simultaneously, the present invention designs a double-layer coating electrode sheet structure. Among them, the first coating selects non-carbon-coated graphite, and the raw material is needle coke, which has a higher graphitization degree, a higher capacity, and a larger maximum compaction density, and can improve the energy density; and the microporous gas-phase silicon carbon material in the first coating can further improve the specific capacity of the active material, and has a smaller volume expansion and contraction during the cycle compared with the silicon monoxide material in the second coating, and has a higher cycle stability. The second coating selects carbon-coated graphite. After carbon coating, the surface graphitization degree weakens, and in the Raman spectrum, I D / I GIncreases, the kinetic performance of lithium deintercalation is enhanced, and the carbon-coated graphite raw material is petroleum coke, with more mosaic structures and better isotropy, which also helps to improve the kinetic performance. The silicon monoxide material paired with it has a lower capacity and cycling stability compared to the microporous gas-phase silicon-carbon material of the first coating, but its kinetic performance is better, especially showing a lower DC internal resistance at the end of discharge, improving the fast charging performance. On the other hand, the particle strength of the active material in the second coating of the present invention is higher than that of the first coating, which can well conduct the force downward during the rolling of the electrode sheet, improve the processing stability of the electrode sheet, obtain an electrode sheet with a larger tap density, and improve the energy density of the battery.
[0060] Preferably, the specific capacity of the non-carbon-coated graphite is 352 - 358 mAh / g. Exemplarily, the specific capacity of the non-carbon-coated graphite is any value among 352 mAh / g, 354 mAh / g, 356 mAh / g, 358 mAh / g or any value within the range formed by any two of the above values.
[0061] Preferably, the maximum tap density of the non-carbon-coated graphite is 1.65 - 1.75 g / cm 3 . Exemplarily, the maximum tap density of the non-carbon-coated graphite is 1.65 g / cm 3 , 1.67 g / cm 3 , 1.69 g / cm 3 , 1.7 g / cm 3 , 1.71 g / cm 3 , 1.73 g / cm 3 , 1.75 g / cm 3 or any value within the range formed by any two of the above values.
[0062] Preferably, the I D / I G value in the Raman spectrum of the non-carbon-coated graphite is 0.1 - 0.3. Exemplarily, the I D / I G value in the Raman spectrum of the non-carbon-coated graphite is any value among 0.1, 0.2, 0.3 or any value within the range formed by any two of the above values.
[0063] Preferably, the median particle size of the non-carbon-coated graphite is 9 - 18 μm. Exemplarily, the median particle size of the non-carbon-coated graphite is any value among 9 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm or any value within the range formed by any two of the above values.
[0064] Preferably, the non-carbon-coated graphite is single-particle graphite or secondary-particle graphite.
[0065] Preferably, the non-carbon-coated graphite is single-particle graphite.
[0066] As a preference, the non-carbon-coated graphite is needle coke-based graphite.
[0067] As a preference, the specific capacity of the carbon-coated graphite is 343 - 349 mAh / g. Exemplarily, the specific capacity of the carbon-coated graphite is any value among 343 mAh / g, 345 mAh / g, 347 mAh / g, 349 mAh / g or any value within the range formed by any two of the above values. Within this specific capacity range, the carbon-coated graphite has a relatively high first Coulombic efficiency and high charge utilization efficiency, which is beneficial to improving the overall performance and lifespan of the battery.
[0068] As a preference, the maximum tap density of the carbon-coated graphite is 1.55 - 1.65 g / cm 3 ³. Exemplarily, the maximum tap density of the carbon-coated graphite is any value among 1.55 g / cm 3 ³, 1.57 g / cm 3 ³, 1.59 g / cm 3 ³, 1.6 g / cm 3 ³, 1.61 g / cm 3 ³, 1.63 g / cm 3 ³, 1.65 g / cm 3 ³ or any value within the range formed by any two of the above values. Within this maximum tap density range, it can ensure that the battery has a relatively high energy density.
[0069] As a preference, the I D / I G value in the Raman spectrum of the carbon-coated graphite is 0.8 - 1.2. Exemplarily, the I D / I G value in the Raman spectrum of the carbon-coated graphite is any value among 0.8, 0.9, 1, 1.1, 1.2 or any value within the range formed by any two of the above values.
[0070] As a preference, the median particle size of the carbon-coated graphite is 9 - 18 μm. Exemplarily, the median particle size of the carbon-coated graphite is any value among 9 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm or any value within the range formed by any two of the above values. Within this median particle size range, it is beneficial to improving the cycling performance of the battery.
[0071] As a preference, the carbon-coated graphite is single-particle graphite or secondary particle graphite.
[0072] Preferably, the carbon-coated graphite is secondary particle graphite.
[0073] As a preference, the carbon-coated graphite is petroleum coke-based graphite.
[0074] The gas-phase silicon carbon uses porous carbon with a certain pore structure (i.e., the carbon substrate) as the framework, deposits silicon inside the framework by chemical vapor deposition, and finally performs carbon coating. According to the size of the pore structure, the gas-phase silicon carbon includes microporous gas-phase silicon carbon and mesoporous gas-phase silicon carbon. In the present invention, the gas-phase silicon carbon used is microporous gas-phase silicon carbon.
[0075] Preferably, the specific capacity of the microporous gas-phase silicon carbon is 1800-2000 mAh / g. Exemplarily, the specific capacity of the microporous gas-phase silicon carbon is any value among 1800 mAh / g, 1850 mAh / g, 1900 mAh / g, 1950 mAh / g, 2000 mAh / g or any value within the range formed by any two of the above values. Within this specific capacity range, the microporous gas-phase silicon carbon has a high initial Coulombic efficiency and high charge utilization efficiency, which is beneficial to improving the overall performance and lifespan of the battery.
[0076] Preferably, the initial Coulombic efficiency of the microporous gas-phase silicon carbon is 90%-93%. Exemplarily, the initial Coulombic efficiency of the microporous gas-phase silicon carbon is any value among 90%, 91%, 92%, 93% or any value within the range formed by any two of the above values. Within this initial Coulombic efficiency range, the charge utilization efficiency is high, which is beneficial to improving the overall performance and lifespan of the battery.
[0077] Preferably, the median particle size of the microporous gas-phase silicon carbon is 6-10 μm. Exemplarily, the median particle size of the microporous gas-phase silicon carbon is any value among 6 μm, 7 μm, 8 μm, 9 μm, 10 μm or any value within the range formed by any two of the above values. Within this median particle size range, it is beneficial to improving the cycling performance of the battery.
[0078] Preferably, the pore volume of the microporous gas-phase silicon carbon is 0.6-1.0 cm 3 / g. Exemplarily, the pore volume of the microporous gas-phase silicon carbon is any value among 0.6 cm 3 / g, 0.7 cm 3 / g, 0.8 cm 3 / g, 0.9 cm 3 / g, 1.0 cm 3 / g or any value within the range formed by any two of the above values.
[0079] Preferably, the pore diameter of the micropores of the microporous gas-phase silicon carbon is 0.4-2 nm. Exemplarily, the pore diameter of the micropores of the microporous gas-phase silicon carbon is any value among 0.4 nm, 0.6 nm, 0.8 nm, 1 nm, 1.2 nm, 1.4 nm, 1.6 nm, 1.8 nm, 2 nm or any value within the range formed by any two of the above values.
[0080] Preferably, the volume fraction of micropores in the total pore volume of the microporous gas-phase silicon carbide is 90% - 96%. Exemplarily, the volume fraction of micropores in the total pore volume of the microporous gas-phase silicon carbide is any value among 90%, 91%, 92%, 93%, 94%, 95%, 96% or any value within the range formed by any two of the above values.
[0081] In the embodiments of the present invention, the carbon source of the carbon substrate of the microporous gas-phase silicon carbide includes at least one of biomass carbon sources, resin carbon sources, and coke carbon sources.
[0082] Preferably, the specific capacity of silicon monoxide is 1300 - 1500 mAh / g. Exemplarily, the specific capacity of silicon monoxide is any value among 1300 mAh / g, 1350 mAh / g, 1400 mAh / g, 1450 mAh / g, 1500 mAh / g or any value within the range formed by any two of the above values.
[0083] Preferably, the first Coulombic efficiency of silicon monoxide is 89% - 92%. Exemplarily, the first Coulombic efficiency of silicon monoxide is any value among 89%, 90%, 91%, 92% or any value within the range formed by any two of the above values.
[0084] Preferably, the median particle size of silicon monoxide is 4 - 8 μm. Exemplarily, the median particle size of silicon monoxide is any value among 4 μm, 5 μm, 6 μm, 7 μm, 8 μm or any value within the range formed by any two of the above values.
[0085] Preferably, the silicon monoxide is pre-lithiated silicon monoxide and / or pre-magnesium silicon monoxide.
[0086] Preferably, the silicon crystal domain size of silicon monoxide is 5 - 9 nm. Exemplarily, the silicon crystal domain size of silicon monoxide is any value among 5 μm, 6 μm, 7 μm, 8 μm, 9 nm or any value within the range formed by any two of the above values.
[0087] Preferably, the silicon monoxide is pre-lithiated silicon monoxide, and the pre-lithiation method is solid phase or liquid phase, preferably liquid phase, and the lithium silicate phase is mainly Li2SiO3.
[0088] Preferably, the mass fraction of the microporous gas-phase silicon carbide in the first active material is 10% - 50%. Exemplarily, the mass fraction of the microporous gas-phase silicon carbide in the first active material is any value among 10%, 20%, 30%, 40%, 50% or any value within the range formed by any two of the above values.
[0089] Preferably, the mass ratio of silicon monoxide in the second active material is 10% to 50%. Exemplarily, the mass ratio of silicon monoxide in the second active material is any value among 10%, 20%, 30%, 40%, 50% or any value within the range formed by any two of the above values.
[0090] Preferably, the specific capacity of the first active material is 600 to 700 mAh / g. Exemplarily, the specific capacity of the first active material is any value among 600 mAh / g, 620 mAh / g, 640 mAh / g, 660 mAh / g, 680 mAh / g, 700 mAh / g or any value within the range formed by any two of the above values. According to the specific capacity, the mass ratios of non-carbon-coated graphite and microporous gas-phase silicon carbon in the first active material can be obtained. When the specific capacity of the first active material is less than 600 mAh / g, the advantages of the double-layer coating design cannot be reflected; when the specific capacity of the first active material is greater than 700 mAh / g, the electrode will expand too much and the practical value is not high.
[0091] Preferably, the specific capacity of the second active material is 600 to 700 mAh / g. Exemplarily, the specific capacity of the second active material is any value among 600 mAh / g, 620 mAh / g, 640 mAh / g, 660 mAh / g, 680 mAh / g, 700 mAh / g or any value within the range formed by any two of the above values. According to the specific capacity, the mass ratios of carbon-coated graphite and silicon monoxide in the second active material can be obtained. When the specific capacity of the second active material is less than 600 mAh / g, the advantages of the double-layer coating design cannot be reflected; when the specific capacity of the second active material is greater than 700 mAh / g, the electrode will expand too much and the practical value is not high.
[0092] In the embodiment of the present invention, the first coating further includes a first binder and a first conductive agent.
[0093] In the embodiment of the present invention, the second coating further includes a second binder and a second conductive agent.
[0094] In the embodiment of the present invention, the first binder and the second binder independently include type A binders and type B binders. The type A binders include at least one of polyacrylic acid, polyacrylonitrile, sodium carboxymethyl cellulose, and lithium carboxymethyl cellulose. The type B binders include at least one of styrene-butadiene rubber and modified styrene-butadiene polymers. Among them, the type A binders provide greater adhesion and elastic modulus, and the type B binders provide greater toughness. The combined use of type A binders and type B binders can better play the binding role.
[0095] In an embodiment of the present invention, the first conductive agent and the second conductive agent independently include a type-C conductive agent and a type-D conductive agent. The type-C conductive agent includes at least one of single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, and graphdiyne. The type-D conductive agent includes at least one of acetylene black, Ketjen black, Super P, and EnsacoTM. For example, the single-walled carbon nanotube conductive agent in the type-C conductive agent is filamentous, providing certain structural elasticity while having high conductivity, and gathering the active particles together; for example, the acetylene black conductive agent in the type-D conductive agent is dot-shaped and dispersed on the surface of the active particles. The combined use of the type-C conductive agent and the type-D conductive agent can better play the conductive role.
[0096] Preferably, in the first coating, the mass ratio of the first active material, the first binder, and the first conductive agent is (90 - 95):(5 - 10):(1 - 5).
[0097] Preferably, in the second coating, the mass ratio of the second active material, the second binder, and the second conductive agent is (95 - 100):(1 - 5):(0.5 - 1.5).
[0098] Preferably, the ratio of the mass fraction of the first binder in the first coating to the mass fraction of the second binder in the second coating is (1 - 4):1. Exemplarily, the ratio of the mass fraction of the first binder in the first coating to the mass fraction of the second binder in the second coating is any value among 1:1, 2:1, 3:1, 4:1 or any value within the range value composed of any two of the above values. When the electrode sheet is coated and dried, due to the capillary force, the binder will migrate to the surface, and with the increase of the coating speed and the coating thickness, the migration of the binder during the drying process becomes more serious, which will further weaken the adhesion between the dressing and the current collector, having a negative impact on the battery performance. In the double-layer coating structure of the present invention, the first coating slurry uses a higher mass ratio of the binder for compensation in advance, increasing the adhesion between the dressing and the current collector.
[0099] Preferably, the ratio of the mass fraction of the first conductive agent in the first coating to the mass fraction of the second conductive agent in the second coating is (1 - 4):1. Exemplarily, the ratio of the mass fraction of the first conductive agent in the first coating to the mass fraction of the second conductive agent in the second coating is any value among 1:1, 2:1, 3:1, 4:1 or any value within the range value composed of any two of the above values. The first coating has a higher content of the conductive agent, which can form more conductive paths, reduce the electron transfer resistance of the electrode sheet, and improve the battery rate performance and cycle stability.
[0100] Preferably, the mass ratio of the first coating to the second coating is 1:(0.5 - 2). Exemplarily, the mass ratio of the first coating to the second coating is any value among 1:0.5, 1:1, 1:1.5, 1:2 or any value within the range formed by any two of the above values.
[0101] Preferably, the ratio of the porosity of the second coating to the porosity of the first coating is (1 - 2):1. Exemplarily, the ratio of the porosity of the second coating to the porosity of the first coating is any value among 1:1, 1.5:1, 2:1 or any value within the range formed by any two of the above values. When the porosity of the second coating is greater than that of the first coating, it is beneficial to the migration of lithium ions inside the thick electrode, thereby obtaining better electrochemical performance at high current density.
[0102] Preferably, the porosity of the first coating is 20% - 30%. Exemplarily, the porosity of the first coating is any value among 20%, 22%, 24%, 26%, 28%, 30% or any value within the range formed by any two of the above values.
[0103] Preferably, the porosity of the second coating is 20% - 40%. Exemplarily, the porosity of the second coating is any value among 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40% or any value within the range formed by any two of the above values.
[0104] Preferably, the tap density of the negative electrode sheet is 1.5 - 1.7 g / cm 3 . Exemplarily, the tap density of the negative electrode sheet is 1.5 g / cm 3 、1.55 g / cm 3 、1.6 g / cm 3 、1.65 g / cm 3 、1.7 g / cm 3 or any value within the range formed by any two of the above values.
[0105] In the embodiments of the present invention, the current collector is one of copper foil, electrolytic tough pitch copper foil, porous copper foil, nickel foam / copper foil, carbon-coated copper foil.
[0106] The present invention also provides a method for preparing the above negative electrode sheet, comprising the following steps:
[0107] S1, mixing non-carbon-coated graphite and microporous gas-phase silicon carbon to prepare a first coating slurry;
[0108] S2, mixing carbon-coated graphite and silicon monoxide to prepare a second coating slurry;
[0109] S3. The first coating slurry and the second coating slurry are coated on the surface of the current collector, and after drying and cold pressing, a negative electrode sheet is obtained.
[0110] Preferably, based on the coating area of 1540.25 mm 2 calculated, the single-sided coating weight of the negative electrode sheet is 50-100 mg. Exemplarily, the single-sided coating weight of the negative electrode sheet is any value among 50 mg, 60 mg, 70 mg, 80 mg, 90 mg, 100 mg or any value within the range formed by any two of the above-mentioned values.
[0111] In a second aspect, the present invention provides a lithium-ion battery, which includes the above-mentioned negative electrode sheet.
[0112] In the embodiments of the present invention, the battery structure includes but is not limited to button cells, soft-pack batteries, cylindrical batteries, etc.
[0113] The present application places no particular restrictions on the positive electrode sheet, separator, and electrolyte in the battery. Those skilled in the art can choose according to actual needs as long as the purpose of the present application can be achieved.
[0114] The reagents, instruments, materials, etc. used in the present invention can all be obtained through commercial channels.
[0115] The following further elaborates the present invention in conjunction with embodiments:
[0116] Example 1:
[0117] (1) Preparation of the first coating slurry:
[0118] The mass ratio of the first active material, styrene-butadiene rubber, polyacrylic acid, single-walled carbon nanotubes, and conductive carbon black (acetylene black) is 91.18:2.24:4.48:0.048:2.052. The first active material is composed of non-carbon-coated single-particle graphite and microporous gas-phase silicon carbon, and its specific ratio is calculated according to their respective capacities to form a composite material with a gram capacity of 650 mAh / g. Among them, the gram capacity of the non-carbon-coated single-particle graphite is 355 mAh / g, and the maximum compaction density is 1.7 g / cm 3 , I D / I G is 0.2, and the median particle size is 15 μm; the carbon source of the microporous gas-phase silicon carbon is a resin-based carbon source, the pore volume is 0.7 cm 3 / g, the micropore proportion is 90%, the median particle size is 8 μm, the gram capacity is 1800 mAh / g, and the first Coulombic efficiency is 93%. The first active material and conductive carbon black are pre-stirred, then 1 / 2 portion of polyacrylic acid and deionized water are added for stirring, then single-walled carbon nanotubes, 1 / 2 portion of polyacrylic acid, styrene-butadiene rubber, and deionized water are added for stirring, and the content of deionized water is adjusted to make the final solid content of the discharged material 52%;
[0119] (2) Preparation of the second coating slurry:
[0120] The mass ratio of the second active material, styrene-butadiene rubber, polyacrylic acid, single-walled carbon nanotubes, and conductive carbon black is 97.42:0.56:1.12:0.072:0.828. The second active material consists of carbon-coated secondary particle graphite and prelithiated silicon monoxide. Its specific ratio is calculated according to their respective capacities to form a composite material with a gram capacity of 650 mAh / g. Among them, the gram capacity of the carbon-coated secondary particle graphite is 346 mAh / g, and the maximum tap density is 1.6 g / cm 3 , I D / I G is 1.0, the median particle size is 15 μm, the silicon crystal domain size of the prelithiated silicon monoxide is 7 nm, the prelithiation method is liquid-phase prelithiation, the median particle size is 8 μm, the gram capacity is 1380 mAh / g, and the first Coulombic efficiency is 91%. The second active material and conductive carbon black are pre-stirred, then 1 / 2 portion of polyacrylic acid and deionized water are added and stirred, then single-walled carbon nanotubes, 1 / 2 portion of polyacrylic acid, styrene-butadiene rubber, and deionized water are added and stirred. The solid content of the final discharge is adjusted to 48% by adjusting the content of deionized water;
[0121] (3) Preparation of the negative electrode sheet:
[0122] The first coating slurry and the second coating slurry are double-coated by die extrusion. The single-sided coating weight of both coatings is controlled to be 50 mg (calculated based on a coating area of 1540.25 mm 2 ). After double-sided coating, it is dried and cold-pressed (tap density 1.6 g / cm 3 ), which is the negative electrode sheet; the porosity of the first coating is 25%, and the porosity of the second coating is 30%;
[0123] (4) Preparation of the secondary battery:
[0124] The negative electrode sheet, separator, and commercial positive electrode sheet are stacked and wound in sequence to obtain a bare battery cell. The tabs are ultrasonically welded. The bare battery cell is placed in a battery case, dried to remove moisture, electrolyte is injected into the battery case, and it is encapsulated. After formation and grading, the secondary battery is obtained.
[0125] Example 2:
[0126] The difference between this example and Example 1 is:
[0127] (1) Preparation of the first coating slurry:
[0128] The pore volume of the microporous gas-phase silicon-carbon carbon substrate is 0.72 cm 3 / g, the microporous proportion is 92%, the gram capacity is 1900 mAh / g, and the first Coulombic efficiency is 92%.
[0129] (2) Preparation of the second coating slurry:
[0130] The silicon crystal domain size of the prelithiated silicon monoxide is 7 nm, the median particle size is 7 μm, the specific capacity is 1400 mAh / g, and the initial Coulombic efficiency is 90%.
[0131] Example 3:
[0132] The difference between this example and Example 1 is as follows:
[0133] (1) Preparation of the first coating slurry:
[0134] The pore volume of the microporous gas-phase silicon-carbon carbon substrate is 0.75 cm 3 / g, the micropore proportion is 94%, the specific capacity is 2000 mAh / g, and the initial Coulombic efficiency is 91%.
[0135] (2) Preparation of the second coating slurry:
[0136] The silicon crystal domain size of the prelithiated silicon monoxide is 5 nm, the median particle size is 6 μm, the specific capacity is 1420 mAh / g, and the initial Coulombic efficiency is 89%.
[0137] Comparative Example 1:
[0138] The difference between this comparative example and Example 1 is as follows: The prelithiated silicon monoxide in the second coating is replaced by microporous gas-phase silicon-carbon. The specific operation is as follows:
[0139] (1) Preparation of the first coating slurry:
[0140] The mass ratios of the first active material, styrene-butadiene rubber, polyacrylic acid, single-walled carbon nanotubes, and conductive carbon black are 91.18:2.24:4.48:0.048:2.052. The first active material consists of non-carbon-coated single-particle graphite and microporous gas-phase silicon-carbon, and its specific ratio is calculated according to their respective capacities to form a composite material with a specific capacity of 650 mAh / g. Among them, the specific capacity of the non-carbon-coated single-particle graphite is 355 mAh / g, the maximum compaction density is 1.7 g / cm 3 , I D / I G is 0.2, the median particle size is 15 μm, the carbon source of the gas-phase silicon-carbon carbon substrate is a resin-based carbon source, the pore volume is 0.7 cm 3 / g, the micropore proportion is 90%, the median particle size is 8 μm, the specific capacity is 1800 mAh / g, and the initial Coulombic efficiency is 93%. The first active material and conductive carbon black are pre-stirred, then 1 / 2 portion of polyacrylic acid and deionized water are added and stirred, then single-walled carbon nanotubes, 1 / 2 portion of polyacrylic acid, styrene-butadiene rubber, and deionized water are added and stirred. The solid content of the final product is adjusted to 52% by adjusting the content of deionized water;
[0141] (2) Preparation of the second coating slurry:
[0142] The mass ratios of the second active material, styrene-butadiene rubber, polyacrylic acid, single-walled carbon nanotubes, and conductive carbon black are 97.42:0.56:1.12:0.072:0.828. The second active material consists of carbon-coated secondary particle graphite and microporous gas-phase silicon carbon, and their specific ratios are calculated according to their respective capacities to form a composite material with a gram capacity of 650 mAh / g. Among them, the gram capacity of the carbon-coated secondary particle graphite is 346 mAh / g, and the maximum tap density is 1.6 g / cm 3 , I D / I G is 1.0, the median particle size is 15 μm, the carbon source of the gas-phase silicon carbon in the carbon base is a resin-based carbon source, the pore volume is 0.7 cm 3 / g, the microporous proportion is 90%, the median particle size is 8 μm, the gram capacity is 1800 mAh / g, and the first Coulombic efficiency is 93%. Pre-stir the second active material and conductive carbon black, then add 1 / 2 portion of polyacrylic acid and deionized water and stir, then add single-walled carbon nanotubes, 1 / 2 portion of polyacrylic acid, styrene-butadiene rubber and deionized water and stir. Adjust the content of deionized water to make the final solid content of the discharged material 48%;
[0143] (3) Preparation of the negative electrode sheet:
[0144] Double-layer coat the first coating slurry and the second coating slurry by die extrusion. Control the single-sided coating weight of the two coatings to be 50 mg each (calculated based on a coating area of 1540.25 mm 2 ), dry after double-sided coating, and cold press (tap density 1.6 g / cm 3 ), to obtain the negative electrode sheet;
[0145] (4) Preparation of the secondary battery:
[0146] Stack the negative electrode sheet, separator, and commercial positive electrode sheet in sequence, wind them to obtain a bare battery core, ultrasonically weld the electrode tabs, place the bare battery core in the battery case, dry to remove moisture, inject electrolyte into the battery case, encapsulate, and perform formation and grading to obtain the secondary battery.
[0147] Comparative Example 2:
[0148] The difference between this comparative example and Example 1 is that: the microporous gas-phase silicon carbon in the first coating is replaced by prelithiated silicon monoxide. The specific operations are as follows:
[0149] (1) Preparation of the first coating slurry:
[0150] The mass ratios of the first active material, styrene-butadiene rubber, polyacrylic acid, single-walled carbon nanotubes, and conductive carbon black are 91.18:2.24:4.48:0.048:2.052. The first active material consists of non-carbon-coated single-particle graphite and pre-lithiated lithium silicate. Their specific ratios are calculated according to their respective capacities to form a composite material with a gram capacity of 650 mAh / g. Among them, the gram capacity of the non-carbon-coated single-particle graphite is 355 mAh / g, and the maximum tap density is 1.7 g / cm 3 , I D / I G is 0.2, the median particle size is 15 μm, the silicon crystal domain size of the pre-lithiated lithium silicate is 7 nm, the pre-lithiation method is liquid-phase pre-lithiation, the median particle size is 8 μm, the gram capacity is 1380 mAh / g, and the initial Coulombic efficiency is 91%. The first active material and conductive carbon black are pre-stirred, then 1 / 2 portion of polyacrylic acid and deionized water are added and stirred, then single-walled carbon nanotubes, 1 / 2 portion of polyacrylic acid, styrene-butadiene rubber, and deionized water are added and stirred. The solid content of the final discharge is adjusted to 52% by adjusting the content of deionized water;
[0151] (2) Preparation of the second coating slurry:
[0152] The mass ratios of the second active material, styrene-butadiene rubber, polyacrylic acid, single-walled carbon nanotubes, and conductive carbon black are 97.42:0.56:1.12:0.072:0.828. The second active material consists of carbon-coated secondary-particle graphite and pre-lithiated lithium silicate. Their specific ratios are calculated according to their respective capacities to form a composite material with a gram capacity of 650 mAh / g. Among them, the gram capacity of the carbon-coated secondary-particle graphite is 346 mAh / g, and the maximum tap density is 1.6 g / cm 3 , I D / I G is 1.0, the median particle size is 15 μm, the silicon crystal domain size of the pre-lithiated lithium silicate is 7 nm, the pre-lithiation method is liquid-phase pre-lithiation, the median particle size is 8 μm, the gram capacity is 1380 mAh / g, and the initial Coulombic efficiency is 91%. The second active material and conductive carbon black are pre-stirred, then 1 / 2 portion of polyacrylic acid and deionized water are added and stirred, then single-walled carbon nanotubes, 1 / 2 portion of polyacrylic acid, styrene-butadiene rubber, and deionized water are added and stirred. The solid content of the final discharge is adjusted to 48% by adjusting the content of deionized water;
[0153] (3) Preparation of the negative electrode sheet:
[0154] The first coating slurry and the second coating slurry are double-coated by die extrusion. The single-sided coating weight of both coatings is controlled to be 50 mg (calculated based on a coating area of 1540.25 mm 2 ), and after double-sided coating, it is dried and cold-pressed (tap density 1.6 g / cm 3 ), to obtain the negative electrode sheet;
[0155] (4) Preparation of secondary battery:
[0156] The negative electrode sheet, separator, and commercial positive electrode sheet are stacked and wound in sequence to obtain a bare battery cell, the tabs are ultrasonically welded, the bare battery cell is placed in a battery case, moisture is removed by drying, electrolyte is injected into the battery case, and then it is encapsulated. After formation and grading, the secondary battery is obtained.
[0157] Comparative Example 3:
[0158] The difference between this comparative example and Example 1 is that the hierarchical design is not adopted. The specific operations are as follows:
[0159] (1) Preparation of coating slurry:
[0160] The mass ratios of the active material, styrene-butadiene rubber, polyacrylic acid, single-walled carbon nanotubes, and conductive carbon black are 94.3: 1.4: 2.8: 0.06: 1.44. The active material consists of microporous gas-phase silicon carbon, pre-lithiated silicon oxide, and artificial graphite, and their specific ratios are calculated according to their respective capacities to form a composite material with a gram capacity of 650 mAh / g. The artificial graphite consists of non-carbon-coated single-particle graphite and carbon-coated secondary-particle graphite, with their respective mass ratios being 50%. Their physical properties are the same as those in Example 1, and the microporous gas-phase silicon carbon and pre-lithiated silicon oxide are the same as those in Example 1. The active material and conductive carbon black are pre-stirred, then 1 / 2 portion of polyacrylic acid and deionized water are added and stirred, then single-walled carbon nanotubes, 1 / 2 portion of polyacrylic acid, styrene-butadiene rubber, and deionized water are added and stirred. The solid content of the final product is adjusted to 50% by adjusting the content of deionized water;
[0161] (2) Preparation of negative electrode sheet:
[0162] The coating slurry is coated on the negative electrode copper foil, and the single-sided coating weight is 100 mg (calculated based on the coating area of 1540.25 mm 2 ), and after double-sided coating, it is dried and cold-pressed (compaction density 1.6 g / cm 3 ), which is the negative electrode sheet;
[0163] (3) Preparation of secondary battery:
[0164] The negative electrode sheet, separator, and commercial positive electrode sheet are stacked and wound in sequence to obtain a bare battery cell, the tabs are ultrasonically welded, the bare battery cell is placed in a battery case, moisture is removed by drying, electrolyte is injected into the battery case, and then it is encapsulated. After formation and grading, the secondary battery is obtained.
[0165] Performance test 1:
[0166] The test methods for the charging gram capacity, discharging gram capacity, first Coulomb efficiency, and the number of cycles at 80% capacity retention rate are as follows:
[0167] During formation charging, it is first charged at a constant current of 0.02C until 3.4V, and then charged at a constant current of 0.1C until 3.75V. During grading, it is first charged at a constant current of 0.5C until 4.25V, and then charged at a constant voltage until the current decreases to 0.05C. It is discharged at a constant current of 1C and 0.2C. The charge and discharge specific capacity are calculated based on the mass of the active material and the charge and discharge capacity. The discharge specific capacity divided by the charge specific capacity gives the first Coulomb efficiency. The results are shown in Table 1.
[0168] At room temperature of 25°C, the starting and cut-off voltages are 2.8V and 4.25V. It is charged at 1C until 4.25V, and then charged at a constant voltage of 4.25V until the current decreases to 0.05C. It is discharged at 1C until 2.8V. The ratio of the discharge capacity per cycle to the initial discharge capacity is recorded, and the number of cycles at 80% capacity retention is recorded. The results are shown in Table 1.
[0169] Table 1 Specific capacity, first Coulomb efficiency, and cycle stability
[0170]
[0171] As can be seen from Table 1, the charge specific capacities of the examples and the comparative examples are relatively close, but the discharge specific capacities are slightly different, due to the different first Coulomb efficiencies of each group. The first Coulomb efficiencies of Examples 1-3 are about 86.2%. In Comparative Example 1, since both the upper and lower layers are microporous gas-phase silicon carbide, the first Coulomb efficiency is slightly reduced. In Comparative Example 2, both the upper and lower layers are pre-lithiated silicon monoxide, and the first Coulomb efficiency is slightly increased. In Comparative Example 3, it is not double-layer coated, but the materials used are the same as those in Example 1, and the difference in the first Coulomb efficiency is not significant.
[0172] In terms of cycle stability, the cycle stability of microporous gas-phase silicon carbide is much higher than that of pre-lithiated silicon monoxide. Therefore, Comparative Example 1 has the highest cycle stability, Comparative Example 2 has the lowest, and Comparative Example 3 is in the middle. It is worth mentioning that due to the structural design of double-layer coating in the examples, the cycle stability is higher than that of Comparative Example 3. This is mainly because the microporous gas-phase silicon carbide with better cycle stability is placed in the lower layer, with less swelling, reducing the risk of cyclic delamination between the current collector, enhancing the conductivity, and improving the cycle stability.
[0173] Performance Test 2:
[0174] Fast charging performance test:
[0175] When winding the battery cell, add a separator, and then place a copper wire between the two separators to make a three - electrode. After lithium plating the three - electrode with a small current, conduct tests. At room temperature, discharge at a constant current of 1C to 2.5V, charge at a constant current of 1C to 4.25V, then charge at a constant voltage of 4.25V until the current decreases to 0.05C, discharge at a constant current of 1C to 2.5V (recorded as the measured capacity C0). After full charge, adjust the discharge power to 10% SOC and perform step - charging. Charge at a constant current of 4C, 3.8C, 3.5C, 3C, 2.5C, 2C, 1.8C, 1.5C, 1C, 0.5C, 0.33C in sequence. When the negative reference potential is less than or equal to 0V, change to a smaller rate for charging until the sum of the step - charging capacities is greater than or equal to 0.7C0, then stop the test, count the step - charging time at 10 - 80% SOC, calculate the charging rate, and the results are as Figure 1 shown.
[0176] As can be seen from the figure, the step - charging rates of all examples are relatively high, that is, they have better charging performance.
[0177] For Comparative Example 1, both the upper and lower layers are microporous gas - phase silicon carbide. Although it has the best cycle stability, its charging performance is poor;
[0178] Comparative Example 2 has the highest charging ability, thanks to both the upper and lower layers being pre - lithiated silicon monoxide, but its cycle stability is poor;
[0179] Compared with Example 1, Comparative Example 3 does not adopt the double - layer structure design, and the step - charging rate is relatively low. The comparison between Comparative Example 3 and Example 1 shows the design advantages of the double - layer coating. Example 1 has relatively high charging ability and utilization of specific capacity. It gives full play to the advantages of each component in the active material without forming interactive disadvantages, verifying the superiority of the structure design.
[0180] The above are only the preferred embodiments of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the principle of the present invention, several improvements and refinements can be made, and these improvements and refinements should also be regarded as the protection scope of the present invention.
Claims
1. A negative electrode sheet, characterized in that: The negative electrode sheet comprises a current collector, a first coating layer and a second coating layer, wherein the first coating layer is disposed on two surfaces of the current collector in a thickness direction, and the second coating layer is disposed on a surface of the first coating layer away from the current collector; The first coating layer includes a first active material, and the first active material includes non-carbon-coated graphite and microporous fumed silicon carbon; The second coating layer includes a second active material, and the second active material includes carbon-coated graphite and silicon oxide.
2. The negative electrode sheet according to claim 1, characterized in that: The non-carbon-coated graphite has a gram capacity of 352-358 mAh / g and a maximum compaction density of 1.65-1.75 g / cm 3 , Raman spectroscopy I D / I G The value is 0.1 to 0.3, and the median particle size is 9 to 18 μm; And / or, the non-carbon-coated graphite is single-grain graphite or secondary-grain graphite; Preferably, the non-carbon-coated graphite is single-particle graphite; And / or, the non-carbon-coated graphite is needle coke graphite.
3. The negative electrode sheet according to claim 1, characterized in that: The carbon-coated graphite has a gram capacity of 343 to 349 mAh / g and a maximum compaction density of 1.55 to 1.65 g / cm 3 , Raman spectroscopy I D / I G The value is 0.8 to 1.2, and the median particle size is 9 to 18 μm; And / or, the carbon-coated graphite is single-grain graphite or secondary-grain graphite; Preferably, the carbon-coated graphite is secondary particle graphite; And / or, the carbon-coated graphite is petroleum coke graphite.
4. The negative electrode sheet according to claim 1, characterized in that: The microporous gas phase silicon carbon has a gram capacity of 1800 to 2000 mAh / g, a first coulomb efficiency of 90% to 93%, and a median particle size of 6 to 10 μm; And / or, the pore volume of the microporous gas phase silicon carbon is 0.6 to 1.0 cm 3 / g, the pore size of the micropores of the microporous gas-phase silicon carbon is 0.4-2nm, and the volume proportion of the micropores in the total pore volume of the microporous gas-phase silicon carbon is 90%-96%; And / or, the carbon-based carbon source of the microporous fumed silicon carbon includes at least one of a biomass carbon source, a resin carbon source, and a coke carbon source.
5. The negative electrode sheet according to claim 1, characterized in that: The gram capacity of the silicon oxide is 1300-1500 mAh / g, the first coulombic efficiency is 89%-92%, and the median particle size is 4-8 μm; And / or, the silicon oxide is pre-lithium silicon oxide and / or pre-magnesium silicon oxide; And / or, the silicon domain size of the silicon monoxide is 5 to 9 nm.
6. The negative electrode sheet according to claim 1, characterized in that: The mass proportion of the microporous gas-phase silicon carbon in the first active material is 10% to 50%; And / or, the mass proportion of silicon 2 oxide in the second active material is 10% to 50%; and / or, the gram capacity of the first active material is 600 to 700 mAh / g; And / or, the gram capacity of the second active material is 600-700 mAh / g.
7. The negative electrode sheet according to claim 1, characterized in that: The first coating layer also includes a first binder and a first conductive agent; The second coating layer also includes a second binder and a second conductive agent; and / or, the first adhesive and the second adhesive independently include a type A adhesive and a type B adhesive; The type A binder includes at least one of polyacrylic acid, polyacrylonitrile, sodium carboxymethyl cellulose, and lithium carboxymethyl cellulose; The type B binder includes at least one of styrene-butadiene rubber and modified styrene-butadiene polymer; And / or, the first conductive agent and the second conductive agent independently include a type C conductive agent and a type D conductive agent; The C-type conductive agent includes at least one of single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, and graphyne; The type D conductive agent includes at least one of acetylene black, Ketjen black, Super P, and EnsacoTM.
8. The negative electrode sheet according to claim 7, characterized in that: In the first coating, the mass ratio of the first active material, the first binder and the first conductive agent is (90-95): (5-10): (1-5); and / or, in the second coating, the mass ratio of the second active material, the second binder and the second conductive agent is (95-100): (1-5): (0.5-1.5); and / or, a ratio of a mass proportion of the first binder in the first coating layer to a mass proportion of the second binder in the second coating layer is (1-4):1; And / or, the ratio of the mass proportion of the first conductive agent in the first coating layer to the mass proportion of the second conductive agent in the second coating layer is (1-4):
1.
9. The negative electrode sheet according to claim 1, characterized in that: The mass ratio of the first coating layer to the second coating layer is 1:(0.5-2); and / or, the ratio of the porosity of the second coating layer to the porosity of the first coating layer is (1-2):1; And / or, the compaction density of the negative electrode sheet is 1.5 to 1.7 g / cm 3 .
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode sheet according to any one of claims 1 to 9.